Utilizing of Square Wave Voltammetry to Detect Flavonoids in the Presence of Human Urine - Adam, Vojtech; Mikelova, Radka; Hubalek, Jaromír; Hanustiak, Pavel; Beklova, Miroslava; Hodek, Petr; Horna, Ales; Trnkova, Libuse; Stiborova, Marie; Zeman, Ladislav; Kizek, Rene (Sensors (Basel, Switzerland), 2007)
About biological affecting of flavonoids on animal organisms is known less,thus we selected flavonoids, flavanones and flavones, and their glycosides, which wereexamined as potential inducers of cytochrome(s) P450 when administrated by gavages intoexperimental male rats. The study was focused on induction of CYP1A1, the majorcytochrome P450 involved in carcinogen activation. The data obtained demonstrate thenecessity of taking into account not only ability of flavonoids to bind to Ah receptor(induction factor) but also to concentrate on their distribution and metabolism (includingcolon microflora) in the body. After that we examined certain flavonoids as potential inducers of cytochrome P450, we wanted to suggest and optimize suitable electrochemical technique for determination of selected flavonoids (quercetin, quercitrin, rutin, chrysin and diosmin) in body liquids. For these purposes, we selected square wave voltannetry using carbon paste electrode. Primarily we aimed on investigation of their basic electrochemical behaviour. After that we have optimized frequency, step potential and supporting electrolyte. Based on the results obtained, we selected the most suitable conditions for determination of the flavonoids as follows: frequency 180 Hz, step potential 1.95 mV/s and phosphate buffer of pH 7 as supporting electrolyte. Detection limits (3 S/N) of the flavonoids were from units to tens of nM except diosmin, where the limit were higher than μM. In addition, we attempted to suggest a sensor for analysis of flavonoids in urine. It clearly follows from the results obtained that flavonoids can be analysed in the presence of animal urine, because urine did not influence much the signals of flavonoids (recoveries of the signals were about 90 %).
Keywords: cancer; flavonoids; cytochrome P450; antioxidant; square wave voltammetry; western blot analysis; carbon paste electrode